Model Pembelajaran Kemampuan Koordinasi Pada Siswa Sekolah Dasar - - Sukadiyanto (Jurnal Pendidikan Jasmani Indonesia, 2005)
The coordination is ability that constituting of basic movement and movementfundamental to various skill of athletic branch. It is require to be taught early possibly thatis since children age. Because learning coordination after passing childhood will get ofmany constraints for learner. Almost all children age there are at formal education level ofelementary school. The goal of physical education at elementary school ought to orientedfor enrichment various skill of all motor determined by ability of coordination. There areseven factors which determined coordination ability, that is: ability to (1) link, (2) differentiate,(3) balance, (4) adapt, (5) find and maintain rhythm, (6) react, and (7) change.Students of elementary school grouped become two groups, first, low group studentconsisting of class of I, II, and III, and second, upper group student consisting of class ofIV, V, and VI. Low group student is play group situation, so that is the best time to putdown base skill of motion. The upper group student is the best time to develop variousskills of athletics. All of the students at elementary school are potential for multi lateraltraining, and construction of various athletic skills.The items of coordination ability consist of recognition of feeling to object, controlling toobject, balance, reacting, and accuracy to object. The principle of study coordination atelementary school were started from easy to difficult, from simple to complex, from lightto heavy. That is needed teacher creativity to create a model of coordination learning. Itcould be exploit the environment as a media and a source of learning.Kata Kunci: Pembelajaran, Koordinasi, Siswa Sekolah dasar.